Uterus didelphys with double vagina diagnosed during third cesarean section: A case report - Namkha Dorji; Sangay Tshering; Tshering Wangden (SAGE Open Medical Case Reports, 2022)
Uterus didelphys is a rare uterine anomaly. It is associated with fetal breech presentation, preterm delivery, and cesarean section. Longitudinal vaginal septum may be associated with uterus didelphys, which may cause dyspareunia and labor obstruction. We report a case of 28-year-old woman whose uterus didelphys and longitudinal vaginal septum were diagnosed during third cesarean section. This case report highlights the importance of routine examination of adnexal structures during cesarean section, so that any unsuspected pathologies in the uterus, tubes, and ovaries are diagnosed.